Immune persistence and booster response of a quadrivalent meningococcal conjugate vaccine (MenACYW-TT) 5 years after primary vaccination of adults at ≥56 years of age - Corwin A. Robertson; Jeffry Jacqmein; Alexandre Selmani; Katherine Galarza; Philipp Oster (Taylor & Francis Group, 2024)
Stage I of this study (NCT04142242) demonstrated the safety and immunogenicity of a booster dose of a licensed quadrivalent meningococcal tetanus toxoid-conjugate vaccine (MenACYW-TT) and immune persistence 3 and 6-7 years after priming in older adults who received either quadrivalent meningococcal polysaccharide vaccine (MPSV4) or MenACYW-TT at ≥56 years of age. Stage II, reported here, assessed the antibody persistence after MenACYW-TT versus MPSV4 priming and the safety and immunogenicity of a booster dose of MenACYW-TT in older adults 5 years after primary vaccination with either MPSV4 or MenACYW-TT. A serum bactericidal assay (hSBA) was used to measure functional antibodies against each serogroup immediately before MenACYW-TT booster vaccination and on day (D) 30 post-booster. Safety was also assessed. Antibody persistence declined 5 years post-primary vaccination, with seroprotection (hSBA titer ≥1:8) rates trending higher in MenACYW-TT- versus MPSV4-primed participants. A robust immune response for all four serogroups was observed on D30 after the MenACYW-TT booster, with higher geometric mean titers and seroprotection rates in MenACYW-TT- versus MPSV4-primed participants. Safety outcomes were similar between the two groups. A single booster dose of MenACYW-TT was well tolerated and immunogenic in older adults, with a higher immune response observed in those primed with MenACYW-TT.